Retrograded Eclogites and Gold Mineralization in the Tomar-Córdoba Shear zone at Algueireiras-Algueireirinhas (Assumar) - Pinto, Luis (2011)
In NE Alentejo, the < 1 - 3 km–wide WNW-ESE-striking Tomar-Córdoba Shear Zone (s.s.) includes Proterozoic, blastomylonitic ortho-, para-gneissic migmatites and (retrograded) eclogites. To the north and south of this belt, the outcropping Late Proterozoic Black Series comprises meta-sedimentary and meta-volcanic rocks that, locally, host orogenic (mesothermal) gold mineralizations. Both the Tomar-Córdoba Shear Zone and the Black Series rocks are intruded by Late Ordovician peralkaline granitic and syenitic gneisses. Deformation/metamorphism occurred during the Variscan orogeny and was, probably, superimposed on former Proterozoic (Cadomian?) events. A Variscan asymmetrical flower structure with outward vergence is centered on the Tomar-Córdoba Shear Zone. This major structure is transpressive, with left-lateral shear and outward thrusts over the Black Series rocks.